Real-world variability in use of bone-modifying drugs for multiple myeloma by payer type. Issue 28 (1st October 2022) - Soni, SOPHIA Monica Monica; Hertler, Andrew Allan
Abstract : 129 Background: The use of bone-modifying agents (BMAs) in multiple myeloma is gold standard. Benefits include prevention of skeletal-related events, reduction in bone pain, and improved progression-free survival. Guidelines recommend that patients with active multiple myeloma receive a BMA for up to two years. Unfortunately, real-world data has shown undertreatment with delays in initiation, interruptions in dosing, and premature discontinuation. These gaps are more pronounced for Black patients. The objective of this study was to describe real-world BMA treatment patterns across different payer types: Medicaid, Medicare, and Commercial/Exchange. Methods: This was a retrospective observational study using oncology prior authorization data from multiple payers in the New Century Health (NCH) database. NCH is specialty risk management company who supported over 107, 000 oncology patients in 2021. All patients with a diagnosis of multiple myeloma, as indicated by the treating provider's office, were included who had a prior authorization request for anti-cancer therapy between January 1, 2021, and December 31, 2021. Use of BMA was defined as having ≥1 authorization request for zoledronic acid or denosumab any time in the prior 24 months. BMA use was also evaluated by payer: Medicaid, Medicare, or Commercial/Exchange. Results: A total of 4774 patients were identified as having active multiple myeloma from January 1, 2021, to December 31, 2021. Fifty-nine percent (59.6%) of patients had at least one authorization request for a BMA submitted by their treating provider any time in the preceding 24 months. While most of the identified patients had Medicare, when request for BMA was disaggregated by payer, meaningful differences were found. For patients with commercial or exchange coverage, 64.6% (281/435) had a BMA requested; for patients with Medicare coverage, 60.1% (2339/3890) had a BMA requested. However, for patients with Medicaid, only 51% (229/449) had a BMA requested. Conclusions: Like other studies, our findings highlight underuse of BMAs in multiple myeloma. Differences in request for BMA across payer types suggests variability in adherence to guidelines may be based on patient insurance. To achieve equitable outcomes, including for patients of lower socioeconomic status, targeted efforts must be put in place to ensure receipt of guideline-directed therapy. A strength of this study is the large population and diversity of patients from practices in 41 states with multiple payer types. However, our analysis is limited by several unknown factors such as patient contraindication to or declination of BMA in past that are not captured in the NCH database. This retrospective study, using a large real-world oncology database, highlights that many patients with multiple myeloma may not be receiving guideline-based BMA therapy and that there are meaningful differences depending on patient insurance type.